Supporting positive behaviour and participation of children with Autism at home, at school, and in the community: understanding not 'managing' behaviour - Joosten, Annette (The Autism Society of Western Australia (Inc), 2011)
Background: Many children with autism are referred for intervention because they engage in behaviours regarded as challenging and that restrict the child, and family from participating in desired daily life activities. Intervention programs often assume one reason for all behaviour e.g. sensation seeking, or focus on eliminating rather than understanding the behaviour. This paper is based on research investigating the motivation for behaviour of children with autism and on the author’s experiences working as an occupational therapist with children and families. Aim/Purpose: To provide evidence that (a) there are many reasons for behaviour regarded as challenging and the motivation may change over time and, (b) an individual may engage in the same behaviour for various reasons depending on the context in which the behaviour occurs and, (c) individuals may engage in the same behaviour as others but for different reasons and, (d) anxiety is a frequent motivator for behaviour regarded as challenging. Method: Using a revised Motivation Assessment Scale and the Sensory Profile we assessed the behaviours of children with autism and children with intellectual disability (aged 5-18 years; mean age 9.5 years). Data from 276 MAS:R forms and 52 Sensory Profiles were collected and analysed using Rasch analysis.Findings/Results/Discussion: Children with autism were more likely than children with intellectual disability to engage in behaviours in response to anxiety ( p < 0.001) and, (b) to reduce anxiety, rather than just because they were seeking sensory input (p < 0.03). The form, frequency and motivation for behaviour changed depending on the context. Transition between tasks and environments was most likely to result in behaviours motivated by anxiety. In addition to anxiety and sensation seeking motivators the children were also motivated for other extrinsic reasons, including attention seeking behaviour, a desire to gain a desired object or to escape a situation.